Investigation of poisoning incident caused by datura stramonium in Shuozhou city - LI Xiaohua; PAN Yifu; HAN Shiming (Zhongguo shipin weisheng zazhi, 2023)
ObjectiveTo provide reference for the prevention， control and investigation of similar incident in the future， a poisoning incident caused by datura stramonium was investigated.MethodsAccording to “Technical guideline for epidemiological investigation of food safety incidents” and “Diagnostic criteria and principles of management for food poisoning of datura stramonium （WS/T 3—1996）”， on-site epidemiological investigation， food hygiene investigation， laboratory testing and results determination were carried out.ResultsSixty four cases were poisoned in the incident with attack rate of 60.95% （64/105）. The main symptoms were dry mouth， fatigue， headache， nausea， vertigo， dilated pupils， blurred vision and difficulty to speak. The mean incubation period was 2 h （0.5-5.5 h）. Atropine and scopolamine were detected in the suspicious food remains （yellow cakes） and the raw glutinous broom corn flour， the blood and vomit of cases. The stalks， fruits and seeds of datura stramonium were found in the glutinous broom corn planting land.ConclusionThe incident was a food poisoning incident caused by the glutinous broom corn being harvested with datura stramonium. It is suggested that publicity and education should be carried out to improve farmers’ ability to identify wild toxic plants. Strengthening field management and clean up toxic plants before mechanical harvesting is critical to avoid the recurrence of such incident.